The Acculturation of New Santri in the Culture of Islamic Boarding Schools (A Case Study of Al-Fattahiyyah Islamic Boarding School, Boyolangu, Tulungagung) - Melati Khoirun Nikmah; Bachrul Ulum (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
The diversity of social, cultural, and behavioural backgrounds among newly enrolled students in Islamic boarding schools often creates adaptation challenges, particularly in pesantren that integrate salafiyah traditions with modern educational approaches. This study aims to examine the acculturation process of new santri at Al-Fattahiyyah Islamic Boarding School, Boyolangu, Tulungagung, and to identify the factors influencing their successful adaptation to the pesantren environment. A qualitative approach with a case study design was employed. Participants were purposively selected and included newly enrolled santri as primary informants, supported by pesantren administrators, senior santri, and caregivers. Data were collected through observation, in-depth interviews, and documentation and analyzed using the Miles and Huberman model, consisting of data condensation, data display, and conclusion drawing. The findings reveal that acculturation occurs gradually through several interconnected stages, including environmental introduction, social interaction, adjustment to institutional rules and routines, and the eventual acceptance and internalization of pesantren values. Internal factors, including age, personality, motivation, and attitudes, as well as external factors, including cultural background, social environment, institutional systems, and previous experiences, significantly shape students’ adaptation processes. The study concludes that acculturation among new santri is a dynamic sociocultural process that extends beyond institutional compliance and contributes to the internalization of religious values, discipline, independence, and social responsibility. This study contributes to Islamic education and pesantren studies by highlighting acculturation as a structured yet relational process of value internalization. Its practical implications emphasize the need to strengthen orientation programmes, mentoring systems involving senior santri, and socio-emotional support mechanisms to facilitate more effective and humane adaptation within Islamic boarding school environments.